Leptin and its role in pregnancy and fetal development — an overview. (May 2001) - Reitman, M. L.; Bi, S.; Marcus-Samuels, B.; Gavrilova, O.
Abstract : Leptin is a hormone that is secreted by adipose cells in proportion to adipose mass, and therefore a low leptin level signifies depletion of energy stores. It has been proposed that leptin is one of the signals controlling sexual maturation. For example, humans and rodents lacking leptin fail to undergo complete puberty, while overexpression of leptin in mice causes early puberty. The placenta also produces leptin in human pregnancy, increasing the amount in the maternal circulation. The effects of the increased leptin levels during pregnancy are not clear. In contrast, the mouse placenta does not produce endocrinologically significant amounts of leptin. The mouse placenta does secrete a leptin-binding protein, the production of which correlates with a large increase in maternal leptin levels. The physiology of leptin during pregnancy and fetal development differs significantly between species, and is not well understood in any.